Revitalizing Da'wah Literacy in Islamic Boarding Schools: An ADKAR Model Analysis of the FLP Semar Branch, Pamekasan - St. Ida Noer Laili; Tawvicky Hidayat (Al-Amru: Jurnal Komunikasi dan Dakwah Islam, 2026)
The low level of reading and writing literacy in Indonesia has driven the FLP Semar Branch at Nurul Islam Boarding School to revitalize its role in developing written da'wah. This study examines the revitalization strategies, as well as the supporting and inhibiting factors, using a qualitative descriptive case study approach. Data were collected through interviews, observations, and documentation and analyzed using the ADKAR theory. The findings reveal that revitalization efforts involve organizational evaluation, restructuring, member recruitment, literacy program development, and capacity building through publications and writing activities. Organizational strengthening is reflected in the achievements of its members, although challenges remain, such as time constraints, limited facilities, and fluctuating member enthusiasm. This study highlights the importance of sustainable strategies in promoting written da'wah literacy within the boarding school environment.